Risk factors for poor outcomes in patients with drug-resistant tuberculosis: a 6-year multicenter prospective study in Zhejiang, China - Xuewen Feng; Li Hong; Zhongkang Ji; Cheng Ding; Yanwan Shangguan; Wanru Guo; Songhua Chen; Zebao He; Ying Zhang; Bing Ruan; Kaijin Xu (BMC Infectious Diseases)
Abstract Background At present, the disease burden of drug-resistant tuberculosis (DR-TB) is still heavy in the world. In this study, we aimed to evaluate the success rate of DR-TB patients after standardized treatment and to analyze the risk factors for poor outcomes in Zhejiang, China. Methods From 2017 to 2021, all culture-confirmed tuberculosis (TB) patients were prospectively enrolled from three designated TB hospitals in Zhejiang, China. Demographic surveys were conducted in all patients, and drug susceptibility of TB strains was tested by fluorescent polymerase chain reaction probe melting curve analysis (MeltPro). DR-TB patients were treated with WHO recommended standardized treatment according to the type of drug resistance, and the outcomes were thoroughly monitored and tracked until June 2023. Binary logistic regression model was used to analyze the related risk factors of poor outcomes in patients with DR-TB. The patients' socio-demographic information, comorbidities, fever, antibiotic use, laboratory test results, lung imaging characteristics and drug resistance characteristics were included in the analysis. A simple TB severity score was developed according to the WHO definition and applied to the analysis. Results Among 1013 patients with confirmed TB, 779 were sensitive to all of the tested drugs (rifampicin, isoniazid, ethambutol, streptomycin and fluoroquinolones), and 234 were resistant to at least one tested drug. Among the 234 DR-TB patients in the study, 50 patients had poor outcomes (23 cases of failure, 13 cases of death, and 14 patients lost to follow-up), 158 patients were successfully treated (125 cases were cured and 33 cases completed treatment), and 26 were referred to other provinces. The overall treatment success rate was 76.0% (158/208). Multivariate analysis showed that age (AOR 1.03; 95%CI 1.01—1.05), previous TB treatment history (AOR 5.03; 95%CI 1.33—18.99), higher TB severity score (AOR 1.48; 95%CI 1.09—2.03), MDR/RR-TB (AOR 8.34; 95%CI 2.99—23.24) and pre-XDR-TB (AOR 9.50; 95%CI 2.24—40.26) were independent risk factors for poor outcomes in DR-TB patients. Conclusions The treatment success rate of DR-TB patients in this study reached that of the WHO standard treatment (75%). Physicians should be alert to the possibility of poor outcomes in DR-TB patients with old age, previous TB treatment history, higher TB severity score, MDR/RR-TB or pre-XDR-TB.